Membangun Pesantren Tangguh Bencana Melalui Literasi Kebencanaan Berbasis Partisipatory Mapping di Kota Malang - Widianto, Ahmad Arif; Agusdian, Rian; Putra, Alfyananda Kurnia; Fatanti, Megasari Noer; Perguna, Luhung Achmad; Dini, Alya Muflihatud; Rahayu, Rezki Citra; Fatimah, Sekar Wulan Noventras Nur (Islamic Management and Empowerment Journal, 2025)
Communities in Islamic boarding schools as educational institutions have great potential to experience and be affected by disasters because they are located in vulnerable areas. One of them is the Al-Furqon Islamic Boarding School in Malang City which is located on the edge of a large river, precisely at the confluence of the Bango River and the Brantas River. This study aims to improve the Preparedness of Islamic Boarding Schools in facing the threat of disaster through Disaster Literacy in the form of three steps, namely 1. Participatory Mapping, 2. Disaster Study, 3. Disaster Simulation. In this study, disaster insight measurements were also carried out by giving pretest and posttest questions. The results of the T Test showed an increase in disaster insight before and after being given Disaster Literacy with an average value of 62 from the previous average value of 43, students and administrators of the Al-Furqon Islamic Boarding School have increased preparedness by carrying out disaster simulations in the Islamic Boarding School environment. The participatory mapping approach in this study can increase literacy and active participation of the Islamic boarding school community in anticipating disasters.